2017
DOI: 10.1016/j.concog.2017.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Imagining possible selves across time: Characteristics of self-images and episodic thoughts

Abstract: Thinking about our possible selves can entail thinking about self-related imagined future events. When remembering and imagining, individuals can use both 1st person (field) and 3rd person (observer) perspectives. There is currently a paucity of research examining the visual perspectives of episodic future thoughts that represent possible selves. We hypothesised that temporally distant self-images would elicit more observer perspectives in episodic thoughts than temporally near self-images and current self-ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 82 publications
1
12
0
1
Order By: Relevance
“…However, unlike memories, observer perspectives are often used more frequently when people imagine future events (Macrae et al, 2015; McDermott, Wooldridge, Rice, Berg, & Szpunar, 2016; Rathbone, Conway, & Moulin, 2011; but see D’Argembeau & Van der Linden, 2004, and De Brigard & Giovanello, 2012). For example, Hamilton and Cole (2017) asked people to retrieve memories and generate possible future events elicited by cues related to their self-image. The researchers found a greater proportion of observer perspectives in future events (irrespective of temporal distance) when compared with past events.…”
Section: Visual Perspective and Imaginationmentioning
confidence: 99%
“…However, unlike memories, observer perspectives are often used more frequently when people imagine future events (Macrae et al, 2015; McDermott, Wooldridge, Rice, Berg, & Szpunar, 2016; Rathbone, Conway, & Moulin, 2011; but see D’Argembeau & Van der Linden, 2004, and De Brigard & Giovanello, 2012). For example, Hamilton and Cole (2017) asked people to retrieve memories and generate possible future events elicited by cues related to their self-image. The researchers found a greater proportion of observer perspectives in future events (irrespective of temporal distance) when compared with past events.…”
Section: Visual Perspective and Imaginationmentioning
confidence: 99%
“…In the scientific literature, expectation generally implies an attempt to predict behavioral consequences. Predictive behavior refers to the behavior that is influenced by expectations about the future, such as future environmental conditions, future actions or simply expectations about how things work in this situation (Abram, Picard, Navarro, & Piolino, 2014;Hamilton & Cole, 2017;Murphy et al, 2015;Anokhin, 1987;Lomov & Surkov, 1980;Mendelevich, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…According to construal level theory, a person imagines the future, relying on abstract or specific events i.e., distant future events are mentally presented in a more abstract way than closer future events (Abram et al, 2014;D'Argembeau & Van der Linden, 2004;Murphy et al, 2015;Trope & Liberman, 2003). Hamilton and Cole (2017) emphasize that in their memories and in imagination people can use the perspectives in first person (acting person) and in third person (observer). They suggested that temporal distant self-images would be more often reflected in episodic thoughts than temporal self-images of the present.…”
Section: Resultsmentioning
confidence: 99%
“…This has created divergent approaches, resulting in multiple concepts with slightly different nuances that are used to discuss the phenomenon. For example, mental time travel (Suddendorf & Busby, 2005) and possible selves (Hamilton & Cole, 2017) are used in psychology, imagined futures in sociology (Beckert, 2016), futures consciousness (Ahvenharju, Minkkinen, & Lalot, 2018) and future images (Rubin, 2013) in futures studies and future orientation (Seginer, 2009;Trommsdorff, 1983) across disciplines. In this study, young people do not think about their own future, but reflect on their experiences and views while envisioning the future of schools in general.…”
Section: Future Imagesmentioning
confidence: 99%